Implementation of Rfid in Inventoy Management - et. al., Rajkumar Sharma , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Radio frequency detection has been one of the most developed and anticipated technologies in recent years. RFID is an automated framework for identification that uses RFID tags or navigation systems for remote storage and retrieval of data. RFID is perhaps the most exponentially evolved supply chain management technology. They are also used to integrate different processes that are part of daily operations and to optimize transport of goods across the production process. RFID facilitates real-time tracking of production, inventory prices and demand. On the other hand, the RFID solution is actually costly, unstandardized; manufacturers who undertake sequential projects are less in number and are dissatisfied with privacy concerns. This article explores the benefit and drawbacks of these labels in inventory management.